2017
DOI: 10.2196/mhealth.8651
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone App to Reduce Sugar-Sweetened Beverage Consumption Among Young Adults in Australian Remote Indigenous Communities: Design, Formative Evaluation and User-Testing

Abstract: BackgroundThe disproportionate burden of noncommunicable disease among Indigenous Australians living in remote Indigenous communities (RICs) is a complex and persistent problem. Smartphones are increasingly being used by young Indigenous adults and therefore represent a promising method to engage them in programs seeking to improve nutritional intake.ObjectiveThis study aimed to consult RIC members to inform the content of a smartphone app that can be used to monitor and reduce sugar-sweetened beverage intake … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…Our findings agree to a large extent with previous work in the design of app interventions, as we uncovered user preferences to emphasize a user-centered design [35,36], including particular emphasis on the importance of inclusion of games [35] and on the protection of user privacy [36].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings agree to a large extent with previous work in the design of app interventions, as we uncovered user preferences to emphasize a user-centered design [35,36], including particular emphasis on the importance of inclusion of games [35] and on the protection of user privacy [36].…”
Section: Discussionsupporting
confidence: 89%
“…As shown in Table 3, 11 (34%) sources were from the USA [15][16][17][18][19][20][21][22][23][24][25] and nine (28%) sources were from New Zealand [26][27][28][29][30][31][32][33][34], with the remainder from Australia (12, 38%) [35][36][37][38][39][40][41][42][43][44][45]. As there were no studies from Canada, the findings reported from here on pertain to New Zealand, the USA and Australia.…”
Section: Characteristics Of Sourcesmentioning
confidence: 81%
“…The majority of the interventions used in these studies were interactive websites (n = 21, of 25 interventions in the 32 studies, 84%), providing education modules and tutorials [15, 16, 19, 22, 25-27, 29, 36], screening and assessment tools [18,21], management and monitoring tools [20,23,28,34,38], gamified avatar-based cognitive behaviour therapy (CBT) [31,32] and decision support tools [24,30]. Seven sources reported the use of mobile "apps" [17,33,39,[41][42][43]45], two sources incorporated the use of text or multimedia messaging service [35,40] and two sources studied an intervention that used a mixture of intervention tools [37,44]. Most interventions were self-directed (n = 19, 61.3%), requiring the user to access the WBTI program, often according to a pre-defined schedule, without support from an outside agency or healthcare worker [16, 18, 19, 21-26, 29-34, 37, 38, 41, 42, 45].…”
Section: Types Of Wbti Usedmentioning
confidence: 99%
“…Previous studies recommend conducting usability testing with potential users prior to outcome assessment in studies involving larger samples [48,79,80]. The think-aloud method is commonly used as a usability testing approach among adults [81-83]. However, there are limited references in the literature describing the think-aloud approach in youth usability testing, and most have been conducted with older youth [46,84].…”
Section: Discussionmentioning
confidence: 99%